Ocular Biometry and Anthropometric Measurement in Senile Cataract Patients - Wardany, Yulia; Firdiansyah, Verzy; Putri, Rahmi Triana; Nurman, Efhandi (Frontiers on Healthcare Research, 2026)
Background: Senile cataract is an age-related lens opacity and remains a leading cause of visual impairment. Accurate ocular biometry is essential before cataract surgery to determine appropriate intraocular lens (IOL) power. Ocular biometric factors may be influenced by anthropometric traits such as height, weight, and body mass index (BMI). This study aimed to explore the relationship between ocular biometry and these anthropometric characteristics in patients with senile cataracts Methods: This retrospective analytic study used a cross-sectional design and included 1,466 senile cataract patients treated at a private hospital in Pekanbaru between June 2020 and January 2022. The anthropometric variables included height, body weight, and BMI, while ocular biometry measurements comprised axial length (AL), anterior chamber depth (ACD), keratometry (K), and central corneal thickness (CCT). Pearson correlation analysis was used to assess bivariate associations, and multivariate linear regression analysis was performed to determine independent relationships, controlling for age and gender. Due to collinearity between body weight and BMI, the latter was excluded from the final regression model. Results: Height was positively correlated with AL (p < 0.001, r = 0.281) and ACD (p < 0.001, r = 0.157), and negatively with K (p < 0.001, r = −0.238). Body weight showed positive correlations with AL (p < 0.001, r = 0.210), ACD (p < 0.001, r = 0.149), and CCT (p = 0.010, r = 0.067), and a negative correlation with K (p < 0.001, r = −0.188). BMI demonstrated similar, albeit weaker, correlations. Age was negatively correlated with AL, ACD, and CCT. In multivariate analysis, height and body weight remained independently associated with AL and K, with body weight also independently linked to ACD. Conclusion: Anthropometric parameters, particularly height and body weight, were independently associated with ocular biometric parameters in patients with senile cataracts. These findings suggest that body size and weight may influence ocular structural characteristics relevant to intraocular lens power calculation.